1997
DOI: 10.1055/s-2007-1004157
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection of Submucosal Tumor of the Esophagus: Results in 62 Patients

Abstract: This method of endoscopic removal of submucosal tumors of the esophagus appears to be safe and effective in experienced hands. It allows complete histopathological workup, and at the same time complete removal of the tumor. The method can be considered as an alternative to surgery in symptomatic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
2
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 0 publications
1
37
2
3
Order By: Relevance
“…Bleeding occurred in 9% of the patients in the series of Kojima et al [13], in 4.8% in the series of Hyun et al [10]; and in 16% and 13% in the series of Wei et al [20] and Hunt et al [9], respectively. All cases of bleeding were successfully managed by endoscopy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bleeding occurred in 9% of the patients in the series of Kojima et al [13], in 4.8% in the series of Hyun et al [10]; and in 16% and 13% in the series of Wei et al [20] and Hunt et al [9], respectively. All cases of bleeding were successfully managed by endoscopy.…”
Section: Discussionmentioning
confidence: 98%
“…No important complications were reported, and the ulcer was shown to be cured in 2-4 weeks. Hyun et al [10] reported the resection of 62 tumors, all of them located in the esophagus. Resection was complete in 98% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic submucosal resection (ESMR) has been reported to be effective for the treatment of SETs (12)(13)(14)(15) and it is usually reserved for lesions that are confined to the submucosal or mucosal layers, due to the increased risk of perforation associated with ESMR of lesions originating in the MP layer. However, ESMR occasionally requires a large en-bloc resection and secure hemostasis may prove challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have suggested that endoscopic treatment of GI submucosal tumors is a valid alternative to invasion surgery [9][10][11][12]. However, the choice of treatment for GI lipomas is still controversial, because it has been documented that removal of lipomas 2 cm or greater in diameter (large lipoma) is associated with a greater risk of hemorrhage and perforation [13][14][15][16].…”
mentioning
confidence: 99%